Some aspects of anti-corruption in the Republic of Kazakhstan - Daribekov, S.S.; Daribekova, A.S.; Mambetova, S.Sh.; Eskerova, Z.A.; Glukhova, V.I. (BUKETOV BUSINESS REVIEW, 2023)
Object: the article discusses the concepts, assessment of the development of corruption in Kazakhstan. In particular, the authors seek to propose a mechanism for reducing the scale of corruption activities in the Republic of Kazakhstan on the basis of a theoretical justification of the development of corruption. Methods: based on the application of comparative, theoretical analysis, the conclusion is made about the need to reduce corruption by improving its main directions. Findings: corruption offenses are most clearly manifested in the economy of the Republic of Kazakhstan, especially in the field of economic character. One of the priorities of public administration is to reduce corruption offenses in the country’s economy. Measures based on digitalization as a method of anti-corruption rehabilitation will be proposed as reduction mechanisms. Conclusions: in the scientific article presented by the authors, attention was paid to the consideration of the essence of corruption, the areas of development of corruption activities in Kazakhstan were analyzed, and a system of measures to reduce the scale of corruption activities was proposed.